Development of symmetrical double sided linear wobble plate compressor for bus A/C system - Musa, Md. Nor (2006)
symmetrical double-sided two-way ranging (SDS-TWR) is a ranging method that uses two delays that naturally occur in signal transmission to determine the range between two stations.